Scapula revisited: new features identified and denoted by terms using consensus method of Delphi and taxonomy panel to be implemented in radiologic and surgical practice - Al-Redouan, Azzat; Kachlik, David (Journal of shoulder and elbow surgery, 2022)
BACKGROUND: The scapular structures that have not yet been assigned anatomic terms generate a challenge in clinical diagnostics and surgical application, as well as in scientific observation. The aim of this study was to solve the lack in terminology concerning the scapula and the scapular region. METHODS: Observation and description of 29 structures were carried out on both dry scapulae and radiographs of the shoulder joint. In addition, several terms commonly encountered throughout the literature concerning the scapula were revised. A degree of consensus was reached by using the Delphi method surveying the opinions of 21 invited experts in the field. Taxonomy panels and etymology of anatomic terminology were considered in the generation of the proposed terms. RESULTS: The scapula was redefined as a lamina with projecting processes, and several landmarks demarcating certain newly defined topographic spaces were highlighted via 2 rounds of Delphi systematic voting and discussion. The overall level of the peer nominees' consensus was high. Few terms received a neutral opinion. CONCLUSIONS: This study communicates a proposal of 16 new terms defining grossly visible structures on the scapula that have not yet been described by officially recognized terms, including a call to unify 13 previously contributed terms that have not been codified and are often used interchangeably within different surgical and scientific fields. Incorporating these terms into the anatomic nomenclature would facilitate communication accuracy and eliminate ambiguity among clinicians, surgeons, and anatomists.
Keywords: Scapula; Humans; konsensus; lopatka; ramenní kloub; Consensus; Shoulder Joint; lidé